The evolutionary ecology of inbreeding depression in wild plant populations and its impact on plant mating systems - Cheptou, Pierre-Olivier (Frontiers in Plant Science, 2024)
Inbreeding depression, the reduced fitness of inbred relative to outbred individuals was described more than two centuries ago, long before the development of population genetics. Its impact is central to evolutionary ecology and the evolution of mating systems, in particular self-fertilization in hermaphrodites. In the first half of the 20 th century, population genetics revealed a mechanism for inbreeding depression through homozygosity. Numerous theoretical studies have modeled inbreeding depression as a function of genetic architecture and analyzed how it varies with population selfing rates. A major concept in these models is purging, i.e., the purging of recessive deleterious mutations through inbreeding. Consequently, inbreeding depression is expected to decrease with increasing population selfing rates. Along with these theoretical studies, many experimental studies, particularly on plants, have measured inbreeding depression using experimental crosses or directly in the field. The results of these studies have revealed that the evolutionary ecology of inbreeding depression is difficult to capture and that empirical data do not exactly match model predictions, specifically purging efficacy. In addition, the lability of inbreeding depression in natural populations can qualitatively affect the selective role of inbreeding depression in the evolution of mating systems. Recently, several studies have demonstrated the role of epigenetics in shedding new light on the dynamics of inbreeding depression in natural populations. This review provides a general overview of the studies on inbreeding depression and how various angles can help capture its selective role in natural populations.